Coexistent Ipsilateral Internal Carotid Artery Occlusion and Cerebral Venous Thrombosis in Hepatitis C - Karan Seegobin MBBS (Hons); Somphanh Khousakhoun DO; Ryan Crooks MD; Satish Maharaj MBBS; Cherisse Baldeo MD (SAGE Publishing, 2018)
A 58-year-old male, known to have hepatitis C virus (HCV), presented with intermittent headaches and left-sided sensorimotor symptoms. There were no focal neurological deficits on examination. Electrocardiogram was unremarkable. Computed tomography angiography head and neck displayed extracranial right internal carotid artery occlusion. Magnetic resonance imaging showed right cortical vein thrombosis, with hemorrhagic infarction. Echocardiography with bubble study was unremarkable. Hypercoagulable workup was significant for protein S deficiency. He was treated with warfarin for 6 months. Repeat protein S levels remained low 9 months later. The coexistence of arterial and venous thrombotic events gives rise to a limited differential. In this case, it may be related to chronic HCV infection. The underlying pathogenesis is not clear; however, it is possible the patient had chronic high-grade internal carotid artery stenosis, which occluded leading to his presenting symptoms. The cortical vein thrombosis is likely an incidental finding here. The extent by which HCV contributed to the cerebral thrombosis and carotid artery occlusion in our case is not clear; however, the hypercoagulable and atherosclerotic properties of the virus cannot be disregarded. The virus can promote carotid atherosclerosis and cerebral venous thrombosis as well as other venous and arterial thromboembolic events. Furthermore, HCV is associated with impaired venous flow and procoagulant properties, which can fuel a hypercoagulable state. Also of note cirrhosis is associated with protein S deficiency. We recommend considering an underlying hypercoagulable state including both arterial and venous thrombosis in HCV infection.